2004
DOI: 10.1111/j.1934-6093.2004.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Scheduling for a Single Machine System Under Different Setup and Buffer Capacity Scenarios

Abstract: The problem of dynamic scheduling for single machine manufacturing systems has been extensively studied in the past under different setup scenarios, mainly for systems with infinite buffer capacity. This paper addresses a general framework and investigates similarities and differences between policies optimal if setup times and costs are or are not negligible, if buffers have a finite or an infinite capacity. The cost function takes into account of backlog and surplus, but also includes a demand loss component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The time average costs are commonly used as performance indicator, also referred to as time average weighted work in process for manufacturing systems or time average weighted queue lengths. In [1,4,8,11,14], this performance indicator is also considered. The time average costs, given a fixed cycle time T , are given by…”
Section: Time Average Costsmentioning
confidence: 99%
See 4 more Smart Citations
“…The time average costs are commonly used as performance indicator, also referred to as time average weighted work in process for manufacturing systems or time average weighted queue lengths. In [1,4,8,11,14], this performance indicator is also considered. The time average costs, given a fixed cycle time T , are given by…”
Section: Time Average Costsmentioning
confidence: 99%
“…Therefore, the trajectory can include slow-modes at both queues. A special case of this model, with µ 1 = µ 2 and c 1 = c 2 has been studied in [1,4,7,8,11] and it is shown that the optimal policy is a clearing policy, i.e., the server empties a queue and then switches to serve the other queue.…”
Section: Time Average Costsmentioning
confidence: 99%
See 3 more Smart Citations